ANALYSIS OF THE IMPACT OF DIGITAL TECHNOLOGY ON HOTEL OPERATIONS AND MARKETING IN THE INDUSTRIAL ERA 4.0 - R. Soni Sumali; Tuti Iriani; Moh. Abdul Azis Danu Brata; Indah Sugiarti; Mila Karmila (International Journal of Social Science, 2024)
The Industry 4.0 era has brought significant changes to various sectors, including the hospitality industry. This study analyzes the impact of digital technology on hotel operations and marketing, focusing on the implementation of digital tools such as online reservation systems, data analytics, and digital marketing. The research method used is descriptive qualitative with data obtained from literature studies and interviews with hotel managers. The results of the study show that digital technology improves operational efficiency, expands marketing reach, and strengthens customer relationships. However, the implementation of technology also faces challenges such as high costs and the need for human resource training. These findings provide important insights for hotel industry players in utilizing technology to stay competitive in the digital era.